2015
DOI: 10.1039/c4mb00443d
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid biosynthesis revisited: structure elucidation and metabolic engineering

Abstract: Fatty acids are primary metabolites synthesized by complex, elegant, and essential biosynthetic machinery. Fatty acid synthases resemble an iterative assembly line, with an acyl carrier protein conveying the growing fatty acid to necessary enzymatic domains for modification. Each catalytic domain is a unique enzyme spanning a wide range of folds and structures. Although they harbor the same enzymatic activities, two different types of fatty acid synthase architectures are observed in nature. During recent year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
150
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 167 publications
(162 citation statements)
references
References 274 publications
(421 reference statements)
5
150
0
3
Order By: Relevance
“…Cytosolic acetyl-CoA is also used by acetyl-CoA carboxylase to yield malonyl-CoA, a precursor for de novo synthesis of fatty acids (25,26). We have previously shown that acetyl-CoA carboxylase Acc1p regulates homeostasis of nucleocytosolic acetyl-CoA and acetylation of histones and nonhistone proteins in yeast (13).…”
Section: Resultsmentioning
confidence: 99%
“…Cytosolic acetyl-CoA is also used by acetyl-CoA carboxylase to yield malonyl-CoA, a precursor for de novo synthesis of fatty acids (25,26). We have previously shown that acetyl-CoA carboxylase Acc1p regulates homeostasis of nucleocytosolic acetyl-CoA and acetylation of histones and nonhistone proteins in yeast (13).…”
Section: Resultsmentioning
confidence: 99%
“…A wide range of these compounds has known biological sources, since they serve a variety of purposes, e.g., in cell walls, membranes, and protein modifications, but also as energy storage, such as triacylglycerides, as building blocks for primary and 10 secondary metabolites, or even as messenger molecules. 18,47 Previous studies have shown that lipids, such as phospholipids, glycolipids, and triacylglycerides, are released after cell lysis of phytoplankton cells into the bulk water. Subsequent enzymatic digestion then leads to formation of saturated and unsaturated fatty acids.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that the octanoyl precursor of lipoate is synthesized by a type II fatty acid synthesis system. Such systems, in which each step of fatty acid synthesis is catalyzed by discrete individual proteins, have been studied most thoroughly in bacteria, where they provide all of the fatty acid moieties (97). In eukaryotes, mitochondria and plant plastids (such as chloroplasts) contain type II fatty acid synthesis systems encoded by nuclear genes with the proteins targeted to the organelle, usually by N-terminal sequences.…”
Section: Biosynthesis Of Lipoic Acidmentioning
confidence: 99%